2020
DOI: 10.1038/s41419-020-03053-0
|View full text |Cite
|
Sign up to set email alerts
|

FBI-1 enhanced the resistance of triple-negative breast cancer cells to chemotherapeutic agents via the miR-30c/PXR axis

Abstract: The factor that binds to the inducer of short transcripts‐1 (FBI-1) is a transcription suppressor and an important proto‐oncogene that plays multiple roles in carcinogenesis and therapeutic resistance. In the present work, our results indicated that FBI-1 enhanced the resistance of triple-negative breast cancer (TNBC) cells to chemotherapeutic agents by repressing the expression of micoRNA-30c targeting the pregnane X receptor (PXR). The expression of FBI-1 was positively related to PXR and its downstream drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 54 publications
0
36
0
Order By: Relevance
“…( 59 ), Yang et al. ( 60 ), and Li et al. ( 61 ) showed that miR-140-3p, miR-30c, and miR-148a can inhibit the expression of PXR and CYP3A4, respectively, by acting on the 3’UTR of PXR and reduce the elimination of anti-cancer agents in tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…( 59 ), Yang et al. ( 60 ), and Li et al. ( 61 ) showed that miR-140-3p, miR-30c, and miR-148a can inhibit the expression of PXR and CYP3A4, respectively, by acting on the 3’UTR of PXR and reduce the elimination of anti-cancer agents in tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…The use of clinical specimens was approved by the ethics committee of the Beijing Tian Tan Hospital, Capital Medical University. The 30 clinical TNBC specimens (the BRCA mutation subtype) and paired non-tumor tissues were described in our previous publication ( 35 ). The usage of the clinical specimens were with the written consent from patients and all the experiments related to the human-derived materials, including clinical specimens and cell lines, were used in accordance with the Helsinki Declaration with the approval from medical ethic committee of Beijing Tiantan Hospital or the/the Hebei Key Laboratory of the Cancer Radiotherapy and Chemotherapy.…”
Section: Methodsmentioning
confidence: 99%
“…: S1060), was purchased from Selleck Corporation, Houston, Texas, US. The formulations of olaparib used in the cell-based experiments or animal experiments were described in our previous publication ( 35 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatocellular carcinoma (HCC) accounts for the vast majority of liver cancers, representing nearly 75% of all primary liver tumors ( 4 6 ). The geographic regions with the highest incidence of HCC are Asia and Africa, and nearly half of all cases are estimated to occur in China ( 7 10 ). The most effective treatment for liver cancer is presently surgical resection.…”
Section: Introductionmentioning
confidence: 99%